Green synthesis of silver nanoparticle decorated on reduced graphene oxide nanocomposite using clinacanthus nutans and its applications - Dharshini Perumal,; Che Azurahanim Che Abdullah,; Albert, Emmellie Laura; Ruzniza Mohd Zawawi, (Universiti Kebangsaan Malaysia, 2023)
A straightforward approach that uses Clinacanthus nutans leaf extract as a bio-reduction agent has been reported to anchor silver nanoparticles onto graphene oxide (rGO-Ag). The nanocomposite was characterized by using ultraviolet-visible spectroscopy, Fourier transform infrared spectroscopy, field emission scanning electron microscopy with energy-dispersive X-ray spectroscopy, and X-ray diffraction. A qualitative colour transition from yellowish to dark brown confirmed the biosynthesis of rGO-Ag nanocomposite and showed a surface plasmon resonance at 263 nm and 425 nm. Utilizing cyclic voltammetry, the electrochemical characteristics of the rGO-Ag nanocomposite modified screen printed carbon electrodes were examined. The rGO-Ag nanocomposite electrode enhanced anodic current approximately 1.29 times greater compared to silver nanoparticles (AgNPs) and 1.34 times greater compared to graphene oxide (GO). Moreover, rGO-Ag nanocomposites exhibited excellent antibacterial activity against typical Gram-positive (S. aureus) (11.99 ± 0.26 mm) and Gram-negative (E. coli) (11.86 ± 0.29 mm) bacteria. Toxicity was assayed using brine shrimp Artemia salina. The results of hatching and mortality assay demonstrates that AgNPs and rGO-Ag nanocomposite is biocompatible with A. salina at a low dosage (0.001 mg/mL). This work offers a guide for the future synthesis of nanocomposites using green reductants. The as- synthesized nanocomposite shows a promising component for the development of biomedical devices applications.